RELEVANSI KONSEP MAQASHID SYARIAH PADA PEMASARAN SYARIAH DALAM PANDANGAN IMAM ASY-SYATIBI - Lara Aziza Putri; Miftahul Zikri Sy (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the relevance of the concept of maqashid sharia in sharia marketing in the view of Imam Asy-Syatibi. The concept of maqashid sharia was popularized by Imam Asy-Syatibi with the concept of